Humanistic Method dalam Pembelajaran Bahasa Arab - Ela Isnani Munawwaroh (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
Humanism developed during the 16th century. It gives contributions for education, up to language teaching. Some experts have developed humanistic methods in language teaching, they are Counseling Learning Method (CLM) or Community Language Learning (CLL), silent way, suggestopedia and Total Physical Response (TPR) or the comprehension approach. These methods could be used in language teaching as an alternative method to teaching the Arabic language.